Analysis of yttria-stabilised zirconia and aluminium silicate coated piston crown on the engine performance with palm biodiesel / Navin Ramasamy - Navin , Ramasamy (2022)
In this study, the effects of thermal barrier coatings (TBC) with yttria-stabilised zirconia (Y2O3.ZrO2) and aluminium silicate (Al2O3.SiO2) with NiCrAl bond coatings on the engine performance and emission were evaluated using conventional diesel and pure palm oil biodiesel. These materials were coated on the piston crown using plasma spray coating. The findings demonstrated that Y2O3.ZrO2 coatings presented better engine performances in terms of brake thermal efficiency (BTE), and brake specific fuel consumption (BSFC) for both fuels, which was much better than Al2O3.SiO2 coatings. The piston with Y2O3.ZrO2- coated materials (P2D & P2B) achieved the highest BTE (15.94% for P2D, 14.55% for P2B), and lowest BSFC (498.96 g/kWh for P2D, 619.81 g/kWh for P2B). However, Al2O3.SiO2 coatings indicated better emissions with the lower NO, CO, and CO2 emissions for both fuel. It recorded the lowest HC emission due to complete combustion of the fuel in the engine. Hence, it was concluded that the Y2O3.ZrO2 coating could lead to better engine performance. At the same time, Al2O3.SiO2 showed promising low emissions in the first phase. TBC was prepared using a series of mixtures consisting of different blend ratios of Y2O3.ZrO2 and Al2O3.SiO2 via plasma spray coating. The experimental results showed that a TBC mixture with 60% Y2O3.ZrO2 + 40% Al2O3.SiO2 had excellent NO and CO reductions compared to the other blend coated pistons. The findings also indicated that the coating mixture with 50% Y2O3.ZrO2 + 50% Al2O3.SiO2 had the highest BTE and lowest BSFC compared to all other blend coatings. Blends coated with 50% Y2O3.ZrO2 + 50% Al2O3.SiO2 had the highest performance, lowest emission, and highest durability for the diesel engine application. These encouraging findings further proved the significance of TBCs in terms of enhancing the engine performance and emission reductions operated with different types of fuels.